Giant Rashba Splitting in Pb1–xSnxTe (111) Topological Crystalline Insulator Films Controlled by Bi Doping in the Bulk. Issue 3 (17th November 2016) - Volobuev, Valentine V.; Mandal, Partha S.; Galicka, Marta; Caha, Ondřej; Sánchez‐Barriga, Jaime; Di Sante, Domenico; Varykhalov, Andrei; Khiar, Amir; Picozzi, Silvia; Bauer, Günther; Kacman, Perla; Buczko, Ryszard; et al.
Abstract : The topological properties of lead‐tin chalcogenide topological crystalline insulators can be widely tuned by temperature and composition. It is shown that bulk Bi doping of epitaxial Pb1‐ x Sn x Te (111) films induces a giant Rashba splitting at the surface that can be tuned by the doping level. Tight binding calculations identify their origin as Fermi level pinning by trap states at the surface.